Evaluasi Tingkat Kapabilitas Kinerja Layanan TI pada Layanan Internet Bidang A Menggunakan Framework COBIT 5 Domain MEA 01 (Studi Kasus : Satuan Organisasi XYZ – Lembaga ABC) - Mareta Priscilla Darenoh; Augie David Manuputty; Farry Surachman (Jurnal Teknik Informatika dan Sistem Informasi, 2018)
Information technology (IT) has a very important issue to support business activities in the organization. IT for business has a huge impact on the sustainability of the organization. Bidang A's objective in the Indikator Kerja Utama (IKU) is the implementation of reliable information technology, so Bidang A makes Service Level Agreement (SLA) for agreement level of service quality. For Bidang A requires evaluation to assess the level of service performance capability and makes recommendations to IT services that have not achieved (IKU) in the RENSTRA of Satuan Organisasi XYZ. Bidang A started implementing the COBIT 5 framework as the current governance update action. Bidang A has not yet assessed whether the implementation of the COBIT 5 framework on Bidang A's Internet service has gone well, so this evaluation activity is an initial evaluation of IT Service Performance and IT capability level using the COBIT 5 framework as a measurement tool. The domains used in COBIT 5 are Monitoring, Evaluate, and Assess (MEA). MEA01 is used because MEA01 collects, validates, and evaluates IT business and IT process objectives to provide performance transparency, conformity and drive achievement of organizational goals.